Effects of two different removable functional appliances on depth of the posterior airway space: a retrospective cephalometric study = Effekte zweier verschiedener herausnehmbarer funktionskieferorthopädischer Apparaturen auf die Tiefe desextrathorakalen Luftraums : eine retrospektive kephalometrische Studie - Hourfar, Jan (Journal of orofacial orthopedics, 2017)
Objectives: Aim of the study was the comparison of treatment effects upon pharyngeal depth in patients treated with either (1) S-II-appliance or (2) Activator. Methods: Pre- and posttreatment lateral cephalograms of 73 patients were analyzed using a customized set of measurements. According to predefined criteria, patients were either treated with S-II-appliance or Activator. Pharyngeal depth was assessed from cranial to caudal at six levels (P1 to P6). Paired t tests were used for intragroup and t tests for independent samples for intergroup comparisons. Results were considered statistically significant at p ≤ 0.05.Results37 (22 female, 15 male) patients were treated with the S-II-appliance (mean pretreatment age 11.1 ± 1.07 years), and 36 (20 female, 16 male) patients with an Activator (mean pretreatment age 11.3 ± 1.12 years). Mean treatment time was 14 months for the S-II-appliance and 12 months for the Activator. Most measurements at the different levels showed an average increase ranging from approximately 0.5 mm to almost 2 mm. Changes were more pronounced in S-II patients. In contrast to intergroup comparisons, some intragroup comparisons revealed statistically significant differences at levels P5 (p = 0.0062) and P6 (p = 0.0155) in S-II patients and at P1-level (p = 0.0197) in Activator patients. Conclusions: Both appliances similarly led to an increase of the pharyngeal depth. The sites of statistically significant changes differed.